Fatores individuais e ambientais nas práticas preventivas do câncer de mama em mulheres - LIMA, Ana Lívia Pontes de (2014)
Breast cancer is a public health problem whose incidence has risen dramatically in virtually all the world. Currently 45.3% of cases diagnosed in Brazil are in an advanced stage worsening the prognosis. Therefore, the control of breast cancer should prioritize prevention and early detection through recommended tests: self examination (favoring corporal self) clinical examination and mammography as well as monitoring of the risk factors of this disease. Due to the close relationship between early diagnosis and improved prognosis this study aims to examine the practices of prevention of breast cancer in women aged 40 -69 years living in a community of São Luís - MA. This is a descriptive cross-sectional study with a quantitative approach performed in the period April to August 2014 with 265 women aged 40-69 years residing in the Town of Friars in Coroadinho in Maranhão São Luís. The results reveal that most of the women interviewed were aged 40-44 years (28.3%) incomplete primary education (40.4%) are married or in a stable relati onship (52.5%), brown (57, 7%) unemployed (49.8%) with family income less than minimum wage (55.5%). It was evidenced individual risk factors for breast cancer such as early menarche (22.6%) use of oral injectabl e or patch contraceptives (20%) nulliparity (2.6%) and late menopause (42.7%) makes TRH (20.6%). In the analysis of the environmental risk factors observed lower percentages of alcohol consumpt ion (35.1%) and smoking (21.1%) on the other hand the prevailing sedentary lifestyle (78.9%). The interviewees were overweight (44.9%) and abd ominal circumference greater than 88 cm (61.9%). Regarding preventive practice for early detection of breast cancer, considering the age range recommended for each examination, we observed the aged 40 to 49 years 73.1% underwent clinical examination followed by self-examination, while in women 50 and 69 years was the preferred mammography examination (68.3%). Women interviewed 53.2% reported illness in the last year most spontaneously sought medical care (87.6%) with the SUS primary health service referred (74.5%). We conclude that although there is good adherence to preventive practices for breast cancer the need for change in behavioral patterns that can be stimulated through the implementation of comprehensive and intersectoral measures, such as greater public disclosure of existing projects in the area aiming to stimulate physical activity, as this measure is a priority in the control of no ncommunicable chronic diseases such as breast cancer.